Bentuk, Ideologi dan Makna Manenga Lewu Sebagai Upacara Kematian Pasca Penguburan Bagi Penganut Hindu Kaharingan Di Desa Tarantang Kabupaten Kapuas - Eka, Nali (Jayapangus Press, 2024)
Manenga Lewu is a death ceremony still performed by Hindu Kaharingan in Tarantang Village. However, during the onslaught of modernity and the culture of practical and fast-paced life, the Manenga Lewu ceremony threatens its existence, which could become increasingly rare and even abandoned. In addition, the Manenga Lewu ceremony is unique to the post-burial death ceremony, which Hindu Kaharingan generally carries out. This research aims to analyze and provide information about the form, ideology, and meaning of the Manenga Lewu ceremony, which can add insight for the Hindu community about the death ceremony in Tarantang Village, Kapuas Regency. This research uses a descriptive qualitative method that describes the uniqueness of the Manenga Lewu implementation process by looking at the form, ideology, and meaning as a guideline for analysis. The results showed that Manenga Lewu is the second stage of the death ceremony after burial, which is held for seven days or a maximum of three months. This ceremony is not only to provide a place for the spirit of the deceased but also to release the living family from Rutas in the form of bad luck and abstinence. Manenga Lewu is also a ceremony with religious, social, and artistic ideologies. The meaning of Manenga Lewu includes spiritual, cultural, and social aspects. This ceremony characterizes the Hindu community in Mantangai Sub-district, especially in Tarantang Village, which differs from the Hindu Kaharingan community in other areas of Kapuas Regency.